A Collaborative Study of a Proposed International Standard for Tissue Plasminogen Activator (t-PA) - Gaffney, P J; Curtis, A D (Thrombosis and Haemostasis, 1985)
An international collaborative study involving seven laboratories was undertaken to assess which of three lyophilised preparations might serve as an International Standard (I.S.) for tissue plasminogen activator (t-PA). Two of the preparations were isolates from human melanoma cell cultures while one was of pig heart origin. A clot lysis assay was used by all participants in the study.The data suggested that both preparations of human cell origin were comparable, in that their log dose-response lines were parallel, while that of the porcine preparation was not. Accelerated degradation studies indicated that one melanoma extract (denoted 83/517) was more stable than the other and it was decided to recommend preparation 83/517 as the standard for t-PA. The International Committee for Thrombosis and Haemostasis (Stockholm 1983) has recommended the use of this material as a standard and it has been established by the Expert Committee on Biological Standardization of the World Health Organization as the International, Standard for tissue plasminogen activator, with an assigned potency of 1000 International Units per ampoule.
Keywords: Tissue plasminogen activator (t-PA); International Standard; Clot lysis assay